PERAN APLIKASI DANA DALAM MENDORONG PENINGKATAN TRANSAKSI DIGITAL DI MASYARAKAT - Aknis, Bintang Jaya; Fandiyanto, Randika; Melinda, Nabila Adelia; Agustin, Adelia Dwi; Cahyaningati, Dinda Dwi; Ghofiqi, M. Zam-Zam Al; Pratama, Juli Nanda (Fakultas Ekonomi dan Bisnis, 2024)
In Indonesia, many people do not understand the role of Fintech in transactions, especially in the DANA application. People tend to use cash rather than Fintech. Moreover, people in rural areas lack insight into technology, lack literacy, and do not support MSMEs that use Fintech (DANA) This research aims to determine the role of fund applications in encouraging increased digital transactions in society. As well as encouraging readers how important applications are in the economy and the role of fund applications in facilitating transactions, doing business, investment, loans, and others. In this article readers can find out the fund profile starting from the business strategy and history of DANA's development. The method that researchers use is a qualitative descriptive method so that readers can find out some of the information included from some of the data collected, which means the data obtained by researchers is opinions according to several articles that have been included in the bibliography. The conclusion of this research is that we must be aware of how important the role of Fintech (DANA) is in Indonesia, especially in the aspect of improving the economy and digital literacy, because with Fintech MSMEs can be more advanced because they make payments efficient and increase people's digital literacy.